Analysis of Charcoal Producers Perceptions of Its Production, Forest Degradation, and Governance in Wolaita, Southern Ethiopia’s Dry Afromontane Forests - Alemayehu Hido; Abebe Teka; Asabeneh Alemayehu (International Journal of Forestry Research)
The purpose of this study was to assess charcoal producers’ perceptions of forest degradation and investigate governance in the dry Afromontane forests of Wolaita Zone, Ethiopia. It also examines the socioeconomic contribution of charcoal production to livelihood improvement and the effect of charcoal production on forest degradation and biodiversity loss. Three Kebeles (smallest administrative subunits): Galda, Sere Esho, and Mancha Gugara were purposely selected based on their potential for charcoal production. Semistructured questionnaires were used for household surveys, while checklists were provided for the key informants and focus group discussions. From the total 4,739 charcoal producer households in the selected Kebeles, 98 households were randomly selected and interviewed considering time and budget limitations. Besides, 6 key informant interviews with elders, forestry experts, and farmers and 3 focus group discussions were conducted. A simple descriptive statistical tool was used to analyze descriptive statistical data and chi-square at P<0.05 was used to describe the association of forest degradation with socioeconomic characteristics. The findings reveal that charcoal production is dominated by males (68.4%) compared to females, who were within the age range of 20‒43 years. About 59.18% did not attend any formal education and 18.37% attended elementary education. Charcoal production (32.7%) is second, following agricultural expansion (39.8%) in its negative contribution to forest degradation. The majority (76%) of charcoal producers participated in charcoal production at all times throughout the year. The chi-square result shows a significant relationship between monthly incomes, educational status, family size, and gender with charcoal production and forest degradation at (P<0.05). The indigenous trees, Acacia tortilis (34%), Combretum mole (22%), and Terminalia schimperiana (16%), were the most preferred tree species used for charcoal production. Overall, charcoal production has resulted in forest degradation. Charcoal producers have used traditional earth mound kiln technology. Providing alternative energy sources, training, starting rehabilitation programs, and implementing policies and legal frameworks are needed for the sustainable utilization of the resources and to improve the livelihood of the communities.